Adult-onset central nervous system hemophagocytic lymphohistiocytosis: a case report. Issue 1 (December 2015) - Pastula, Daniel; Burish, Mark; Reis, Gerald; Bollen, Andrew; Cha, Soonmee; Ralph, Jeffrey; Douglas, Vanja
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a clinical syndrome with both genetic and acquired causes characterized by elevated cytokine levels, hyperinflammation, and overactivation of lymphocytes and macrophages. It is typically a systemic disease with variable degrees of CNS involvement. Cases with predominantly central nervous system (CNS) involvement are very rare, with the vast majority of these occurring in infants and young children. This report documents a case of adult-onset CNS-HLH involving a middle-aged man. Case presentation A 55 year-old man developed progressive left hemiparesis and aphasia over the course of several months. Brain MRI showed multifocal, mass-like enhancing lesions with increased susceptibility consistent with blood products. An extensive workup for infectious, autoimmune, and neoplastic etiologies was significant only for a markedly elevated serum ferritin at 1456 ng/mL. Two brain biopsies showed a non-specific inflammatory process. The patient was treated empirically with steroids and plasmapheresis, but he continued to suffer a progressive neurological decline and died one year after onset of neurological symptoms. Autopsy revealed profound histiocytic infiltration, perivascular lymphocytosis, and emperipolesis, compatible with CNS-HLH. Conclusion This case report describes an exceedingly rare presentation of an adult patient with CNS predominant HLH. This diagnosis should be considered in the differential diagnosis of adults presenting with progressive brain lesions, even in the absence of typical systemic signs of HLH.